2017
DOI: 10.18352/ijc.749
|View full text |Cite
|
Sign up to set email alerts
|

Co-management of protected areas to alleviate conservation conflicts: Experiences in Norway

Abstract: This paper addresses the perceptions of actors of protected areas in Norway about a co-management regime at the local level. The analysis is based on quantitative data from surveys of actors of eight protected areas in northern Norway. The surveys were undertaken just before a change to co-management in 2010. The results show that the two strongest determinants that explain actors' initial support of the governance change as a means to alleviate conflict are (i) the relationship of actors to the protected area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Other studies have found a lack of support for conservation to be associated with Norwegians’ views of nature as resilient rather than fragile, a lack of trust in science, favorable attitudes towards local-decision making, dependency on natural resources, gender, age and education (women, young and educated people more in favor) [75,91–95]. We confirm some of these results as large portion of property owners and livestock farmers (stakeholders that are likely to have higher resource dependency) were less supportive protection and had lower trust in higher-level environmental authorities.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found a lack of support for conservation to be associated with Norwegians’ views of nature as resilient rather than fragile, a lack of trust in science, favorable attitudes towards local-decision making, dependency on natural resources, gender, age and education (women, young and educated people more in favor) [75,91–95]. We confirm some of these results as large portion of property owners and livestock farmers (stakeholders that are likely to have higher resource dependency) were less supportive protection and had lower trust in higher-level environmental authorities.…”
Section: Discussionmentioning
confidence: 99%
“…Park restrictions can also impact landowner rights or community livelihoods, usually resulting in strong local opposition [28]. Due to these diverse potential sources of opposition as well as the general need for stakeholder involvement, a common response on the governance level is the use of co-management or decentralized structures [29][30][31][32]. In parallel, increased attention has been devoted to the role of protected areas in rural development, especially in regard with tourism [33,34].…”
Section: Background 21 Land-use and Conservation Conflictsmentioning
confidence: 99%
“…Increases in urban development and tourism were also considered a major driver of conflict, particularly in the Spey catchment. A hotspot was identified by stakeholders in the uplands near the local tourism town, where increases in tourism and recreation are impacting on those "wild" spaces which originally attract people there [86], demonstrating that tourism development has the potential to be a key driver of conflict [87]. Other studies have also found that an increase in the recreational use of an area can cause conflict with biodiversity conservation [88,89], or among different recreational users [90].…”
Section: Drivers Of Conflictmentioning
confidence: 99%